Study on TT Vaccination Status of Female Students of Khulna (Medicine Today, 2019)
Introduction: The purpose of giving the TT vaccine to women of childbearing age and to pregnant women is to protect them from tetanus and to protect their newborn infants against neonatal tetanus.Materials and Methods: A descriptive cross-sectional study was done on January, 2017 to find out the TTvaccination status of students of Khulna Government Pioneer Girls College, Khulna. During scheduled time period. Data were collected from 100 respondents selected by purposive type of convenient sampling by face to face interview using a prepared mixed type of questionnaire.Results: Among total respondent’s majority 36(36%) were belonged to 17-19 years of age group. People of our country nowadays more aware of TT vaccination as 97 (97%) of our total respondents had knowledge about TT vaccination. Achievement in TT vaccination coverage has been impressive throughout the country in recent years. It has also been reflected in our study, we had 84(84%) coverage and 55 (42%) of our respondents had completed their vaccination (5doses). Establishment and improvement of infrastructure of government health organizations 70(83.33%) of our study population received vaccination in government organization. Acceptance of TT vaccination has increased to a satisfactory level. In our study TT vaccination coverage was maximum (85.51%) in upper class and only (71.43%) in lower class respondents.Conclusion: Despite high knowledge, completion of recommended doses of TT vaccine was not guaranteed due to stock-outs coupled with detrimental cultural and religious beliefs.That is why large scale study is needed to find out TT coverage among women of reproductive age group (15-49 years) of Bangladesh which can ensure the real scenario as well as factors related to this.Medicine Today 2019 Vol.31(2): 117-119